Cruise CAGE-18-4 - Bünz, Stefan (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2022)
Cruise CAGE18-4 with UiT’s research vessel R/V Helmer Hanssen was carried out to collect cross-disciplinary data for addressing the objectives of the Norwegian Centre of Excellence for Arctic Gas Hydrate, Environment and Climate, CAGE. The cruise was split into two legs with a port call in Longyearbyen. Leg 1 targeted the Vestnesa Ridge on the western Svalbard margin and acquired 2D and 3D high-resolution P-Cable seismic data in close proximity to the Molloy Ridge in order to better understand tectonic impacts on fluid flow and gas hydrate accumulations. Leg 2 continued our investigations of the newly discovered gas seepage field in the Leierdjupet Fault complex (see CAGE17-3 cruise report) focusing on a better understanding of its complex leakage and source-to-sink plumbing system using seafloor photo and video imagery, water and sediment sampling, multibeam mapping and hydroacoustics. The cruise may be known as: CAGE18_4